Levi-Strauss's Myth Structuralism in the Novel Lontara by Windy Joana - Sinta Alfila; Dwi Widayati; Bambang Riyanto (Bahasa Indonesia Prima, 2025)
Myth can be defined as a story or culture of a community that contains religion and passes it on orally, which can influence people's lives. Morphology events relate to the origin of the universe, the first humans, gods, and other supernatural beings. This research discusses mythology as the study of mythical stories, which are often related to the lives of gods and spirits in people's cultures. One of the myths analyzed in this study is the myth of To Manurung in the novel Lontara by Windy Joana, which tells the story of a messenger of God for the Bugis Makassar community. This research aims to describe the myth structure in the novel Lontara through four levels proposed by Lévi-Strauss, namely geographical, economic, sociological, and cosmological levels. The method used in this research is descriptive qualitative. This research refers to Claude Lévi-Strauss' theory of myth structuralism, which identifies four levels in the myth structure, namely geographical, economic, sociological, and cosmological levels. The results of this study show that in the novel Lontara by Windy Joana, there are four levels of myth structure, namely: (1) Geographical Level, (2) Economic Level, (3) Sociological Level, and (4) Cosmological Level.